Respon Kedelai Hitam terhadap Berbagai Jenis Pupuk Organik - Andi Ralle; St Subaedah (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2020)
Increased productivity of black soybeans continues to be pursued by improving appropriate cultivation technologies, including by providing organic fertilizer. This research aimed to assessing the response of growth and production of black soybean plants to various types of organic fertilizers. The study was conducted in the form of a field experiment in Gowa Regency from March-June 2019. The experiment was designed with a randomized completed block design consisting of four treatments, namely: without organic fertilizer, organic fertilizer from rice straw, organic fertilizer from banana stems and organic fertilizer from gamal leaves. Each treatment was repeated four times, so as to get 16 experimental units. The parameters observed were plant height, number of pods per plant, pod weight per plant and pod weight per plot. The results showed that the administration of organic fertilizers obtained better growth and production of black soybeans. Fertilization with organic fertilizer from Gamal leaves obtained the highest yield of black soybean seeds, 2.46 tons ha-1.